Calcium Antagonist Application in Antenatal Preparation of Pregnant Women with the Risk of Dyscoordinated or Excessively Strong Labor Activity Development - Kuzmina, O. A. (Problems of Cryobiology and Cryomedicine, 2008)
For the antenatal preparation of pregnant women with the risk of development of excessively strong and dyscoordinated labor activity there was elaborated a therapeutic complex, oriented to the metabolic process activation in the mother–placenta–fetus system, as well as normalizing the production of steroid hormones, placental proteins and calcium ion concentration in blood. This is expedient to apply the calcium antagonists and Àctovegin preparation for pregnant women antenatal preparation.